Synovial fluid analysis in companion animal medicine - PRASSINOS (N.N. ΠΡΑΣΙΝΟΣ), N. N.; SIDERI (Α.Ι. ΣΙΔΕΡΗ), K. I.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Synovial fluid analysis is an integral part of the diagnostic approach of joint disorders in companion animal medicine. It mainly helps the veterinarian to differentiateinflammatory from non-inflammatory and infectious from noninfectious joint diseases. Routine synovial fluid analysis should include evaluation of the physical characteristics, cytologic and microbiologic examination, mucin clot test and total protein concentration, while specialized tests (glucose concentration, enzyme levels, crystals, pH, immunological studies) are also performed occasionally. This paper describes the methodology of synovial fluid analysis and discusses its interpretation.